The Dynamics of Broken Home Families: Communication Barriers, Determinants, and Their Impacts on Children’s Psychological and Social Development - Mega Sukma Dewi; Lucia Rini Sugiarti; Fendy Suhariadi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to examine the dynamics of broken home families by focusing on communication barriers, the determinants that lead to family disintegration, and their impacts on children’s psychological and social development. Using a descriptive qualitative approach, data were collected through in-depth interviews with individuals who directly experienced the challenges of living in a non-intact family. The findings reveal that communication breakdowns, such as limited emotional dialogue, aggressive interaction patterns, and inadequate channels for expressing needs, serve as initial triggers for prolonged conflicts that eventually result in family separation. Additional determinants include economic pressures, role disharmony, and ineffective conflict resolution. The impacts on children appear in the form of heightened anxiety, reduced self-esteem, altered social behavior, and difficulties establishing secure interpersonal relationships. These findings highlight the importance of healthy family communication and early psychosocial intervention in preventing and mitigating the long-term consequences of broken home situations on children's development.